Interaksi dan Nilai Sosial dalam Novel Bumi Karya Tere Liye - Ahmad Khoirul Umam; Sri Yanuarsih; I Wayan Letreng (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
Literary works are in the form of language-based works of art with aesthetic elements. The form of literary works includes the novel, which is a work of fiction that expresses aspects of humanity more broadly. Social interaction is a dynamic social bond involving individuals and groups of people. Social value is a measure or assessment of the appropriateness of behavior in people's lives. This study uses a literary sociology approach to describe forms of interaction and social values. The formulations discussed are (1) cooperation (2) accommodation (3) assimilation (4) competition (5) contradiction (6) conflict (7) affection (8) responsibility (9) harmony in life. The aim of the research is to objectively describe and describe social interactions and values. The method used is descriptive literature. The subject is the novel Bumi by Tere Liye. Data collection techniques (1) reading (2) marking (3) recording (4) data corpus. The results of the research are (1) cooperation, Papa and Mama look for Raib (2) accommodation, Papa stabilizes Mama and Raib's conflict (3) assimilation, Ali receives strange clothes (4) competition, Ali takes part in the Physics Olympiad (5) contravention, The Black betrays the Putih (6) conflict, Tamus threatens Raib (7) love, Mama advises Raib (8) responsibility, Ilo provides facilities to Raib, Seli and Ali (9) harmony in life, Ilo helps Raib, Seli and Ali.